PREVALENCE OF DEPRESSION AND THE USE OF ANTIDEPRESSANTS AMONG THIRD YEAR MEDICAL STUDENTS OF KHYBER MEDICAL COLLEGE, PESHAWAR - Marwat, Mushtaq Ahmad (Journal of Postgraduate Medical Institute, 2012)
Objective: To evaluate the prevalence of depression and the use of antidepressants among undergraduatemedical students. Methodology: This was a cross-sectional study done in May, 2011 at Khyber Medical College, Peshawaron third year medical students using Zung self-rating depression scale. Results: 29 out of 166 students (17.5%) were revealed having depression. Two out of these 29 students(6.9%) were using antidepressants. Conclusion: Depression is an under-diagnosed and under-prescribed mental illness.